Scrotal reconstruction after Fournier's gangrene - Leandro Ricardo de Aquino Santos; Conrado Reis Costa; Letícia França de Almeida; Jennifer Pfeffer; João Vitor de Mendonça Chaves; Guilherme Canabrava Rodrigues Silva; Leonardo Soares Marques; Bruno de Freitas Belezia (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: Fournier’s gangrene is a polybacterial infection, usually caused by anaerobic and aerobic bacteria, characterized by scrotal and perineal necrotizing fasciitis. Its treatment is based on surgical intervention by excision of the necrotic area and early antibiotic therapy. There are several strategies to reconstruct the defect resulting from debridement, and it should be noted that tissue losses greater than 50% are usually reconstructed with flaps. Methods: Retrospective analysis of the series of cases of scrotal reconstruction after Fournier’s gangrene performed by the authors throughout 2020, totaling eight patients. Results: The most used flap was thigh fasciocutaneous flap, which presented a partial necrosis rate of 14.29%, without total necrosis. In one of the cases, it was possible to reconstruct a spongy urethra with gracilis muscle without fistulization, preventing the patient from undergoing a definitive urethrostomy. As for complications, the occurrence of minor complications that required simple revision procedures was common. The prevalence of 75% of diabetes mellitus in our series is highlighted, which may have negatively interfered with the healing process. Conclusion: Scrotal reconstruction with flaps is important to accelerate wound healing from Fournier gangrene debridement and to maintain the pouch aspect necessary for testicular thermoregulation. Our primary option was thigh fasciocutaneous flap, which proved to be safe. And minor complications were frequent in this series, without compromising the final result.